The Influence Of Competence, Work Environment And Organisational Culture On Nurses' Performance Related To Patient Safety At RSUD Soekardjo Tasikmalaya - Cahyati, Peni; Iwan Somantri; Heri Djamiatul.M; Novi Indriani; Syaukia Adini; Anah Sasmita (Poltekkes Kemenkes Tasikmalaya, 2025)
This study aims to obtain empirical evidence regarding the influence of competence, work environment and organisational culture on nurse performance at Soekardjo Tasikmalaya Hospital. The results of this study can be used as a contribution to the leadership of the Tasikmalaya Soekardjo Hospital to improve nurse performance through improving competence and work environment and organisational culture. The research method used is descriptive and verification analysis. Data collection used is an interview using a questionnaire accompanied by observation techniques. Data collection in the field was carried out in 2019. The data analysis technique uses Path Analysis. The results showed that competence, work environment, organisational culture and nurse performance in general were relatively good. The results showed that competence, work environment and organisational culture simultaneously had a positive and significant effect on nurse performance at Soekardjo Tasikmalaya Hospital. Partially, the competency variable is more dominant in influencing nurses' performance than the work environment and organisational culture.